EKSPERIMEN INOVASI PEMBUATAN DENDENG MENGGUNAKAN DAUN PEPAYA - Rosie Oktavia Puspita Rini; Luthfiah, Attari (JURNAL MANAJEMEN KULINER, 2024)
Papaya plant Carica Papaya L is a plant that offers varieties of health benefits for human body. One of those benefits are; rich in vitamins and minerals, has antioxidants content that is useful in repeling harmful free radicals inside the body, aiding in digestion and maintaining the immune system. Different parts of the papaya plant contain constituents and benefits that can be utilized, namely; the fruit, skin, seeds, leaves and latex.  This research aims to determine wheter there are differences in the quality of papaya leaf dendeng substitution concerning aroma, taste, texture and color based on the preference of the panelist. This research uses the method of experimental qualitative. The data analysis technique employed in this research involves organoleptic test that is divided into two categories; hedonic test and hedonic quality test. The respondents in this reasearch comprise 5 trained panelists and 8 slightly trained panelists. The results that is gained from the panelist assassments are then processed using SPSS 23 One-Way Anova and DMRT. The processed data that has been collected shows there are no significant differences in the aroma, taste, texture and color aspects of the papaya leaf dendeng. The results of the panelist satisfaction level in this experiment is that they liked the papaya leaf dendeng in terms of aroma, taste, texture and color.